Cognitive behavioural therapy and medication for treatment of adolescent depression: a network meta-analysis. Issue 3 (12th May 2023) - Dardas, Latefa Ali; Xu, Hanzhang; Franklin, Michelle Scotton; Scott, Jewel; Vance, Ashlee; van de Water, Brittney; Pan, Wei
Abstract: Background: Cognitive behavioural therapy (CBT) and medication are widely accepted and useful interventions for individuals with depression. However, a gap remains in our current understanding of how CBT directly benefits adolescents with depression. Aims: The purpose of this study was to examine the short- and long-term effectiveness of CBT only, CBT+Medication, or Medication alone in reducing the duration of major depressive episodes, lessening internalizing and externalizing symptoms and improving global functioning. Methods: Data were extracted from 14 unique studies with a total of 35 comparisons. Network meta-analysis was conducted and p -scores, a measure of the extent of certainty that one treatment is better than another, were used to rank treatments. Results: There was no significant difference between any two treatments for depression, nor internalizing or externalizing symptoms. For global functioning, CBT had significantly greater effect at the longest follow-up than CBT+Medication. CBT+Medication had the highest p -score for depression, short- and long-term effects, and internalizing and externalizing symptoms long-term effects. No indication of publication bias was found. Conclusions: Neither modality, CBT nor medication, is superior for treating adolescent depression. However, CBT was superior in improving global functioning, which is essential for meeting developmental goals.